Residency research requirements and the CanMEDS-FM scholar role: Perspectives of residents and recent graduates - Koo, Jonathan (College of Family Physicians of Canada, 2012)
OBJECTIVE: To explore the perspectives of family medicine residents and recent family medicine graduates on the research requirements and other CanMEDS scholar competencies in family practice residency training. DESIGN: Semistructured focus groups and individual interviews. SETTING: Family practice residency program at the University of British Columbia in Vancouver. PARTICIPANTS: Convenience sample of 6 second-year family medicine residents and 6 family physicians who had graduated from the University of British Columbia family practice residency program within the previous 5 years. METHODS: Two focus groups with residents and individual interviews with each of the 6 recently graduated physicians. All interviews were audiotaped, transcribed, and analyzed for thematic content. MAIN FINDINGS: Three themes emerged that captured key issues around research requirements in family practice training: 1) relating the scholar role to family practice, 2) realizing that scholarship is more than simply the creation or discovery of new knowledge, and 3) addressing barriers to integrating research into a clinical career. CONCLUSION: Creation of new medical knowledge is just one aspect of the CanMEDS scholar role, and more attention should be paid to the other competencies, including teaching, enhancing professional activities through ongoing learning, critical appraisal of information, and learning how to better contribute to the dissemination, application, and translation of knowledge. Research is valued as important, but opinions still vary as to whether a formal research study should be required in residency. Completion of residency research projects is viewed as somewhat rewarding, but with an equivocal effect on future research intentions.